Parâmetros curriculares nacionais de matemática para o ensino fundamental: das prescrições ao currículo praticado pelos professores - Kobashigawa, Mutsu-ko (2006)
The aim of the present work was to analyse how the directions introduced by the established curricula, in the present case the National Curricular Parameters (PCN) for Elementary School mathematical area, are being considered, and if they are being interpreted and applied by the teachers. In accordance with a documental research, an analysis was made about the historical trajectory of the curricular reforms of the Brazilian math education and about the relationship between the implementation of the curricular innovations and the teacher´s education. The research work was carried out in two steps. In the first one, a questionnaire was made and used to collect some general informations about the relationship between the teachers and the PCN. In this step, the process involved 67 math teachers from the public school network. These teachers belong to the Educational Directory of the São Vicente Region, with representation of all the municipal districts from this region. In the second step, 33 teachers were selected and distributed in three groups, being each one composed by 11 teachers. Each group took a part in a meeting, when the more specific informations were obtained by using a procedure named focal group. For a more detailed analysis only one group of those groups was selected. The results have shown that, although the teachers reveal to know the orientations found in the PCN, they did not participate with a deep discussion. In many times they have made a contradictory discuss about the subject, making difficult any conjecture about the implementation of the PCN in the classroom. Although there is concordance with some principles such as problem´s solution, connections with subjects from other courses of study, connection with the daily routine and internal articulations, in the practice the teachers showed a great difficulty to implement those ideas. However, they also revealed a great interest into looking for new knowledges, but at the same time they have a certain disappointment about the offered college education